Genome-Wide Identification of Candidate Genes Underlying Soluble Sugar Content in Vegetable Soybean (Glycine max L.) via Association and Expression Analysis - Lu, Wencheng; Sui, Meinan; Zhao, Xunchao; Jia, Hongchang; Han, Dezhi; Yan, Xiaofei; Han, Yingpeng (Frontiers in Plant Science, 2022)
Soluble sugar is a major indicator of the intrinsic quality of vegetable soybean [Glycine max (L.) Merr.]. The improvement of soluble sugar content in soybean is very important due to its health care functions for human. The genetic mechanism of soluble sugar in soybean is unclear. In the present study, 278 diverse soybean accessions were utilized to identify the quantitative trait nucleotides (QTNs) for total soluble sugar content in soybean seeds based on genome-wide association study (GWAS). A total of 25,921 single-nucleotide polymorphisms (SNPs) with minor allele frequencies (MAF) ≥ 5% and missing data ≤ 10% were selected for GWAS. Totally, thirteen QTNs associated with total soluble sugar content were identified, which distributed on ten chromosomes. One hundred and fifteen genes near the 200-kb flanking region of these identified QTNs were considered as candidate genes associated with total soluble sugar content in soybean seed. Gene-based association analysis and haplotype analysis were utilized to further identify the effect of candidate genes on total soluble sugar content. Totally, 84 SNPs from seventeen genes across four chromosomes were signiﬁcantly associated with the total soluble sugar content. Among them, three SNPs from Glyma.02G292900 were identified at two locations, and other eighty-one SNPs from sixteen genes were detected at three locations. Further expression level analysis of candidate genes revealed Glyma.02G293200 and Glyma.02G294900 were significantly positively associated with soluble sugar content and Glyma.02G294000 was significantly negatively associated with soluble sugar content. Six genes (Glyma.02G292600, Glyma.02G292700, Glyma.02G294000, Glyma.02G294300, Glyma.02G294400, Glyma.15G264200) identified by GWAS also were detected by the analysis of differential expression genes based on soybean germplasms with higher and lower soluble sugar content. Among them, Glyma.02G294000 is the only gene that was identified by gene-based association analysis with total soluble sugar content and was considered as an important candidate gene for soluble sugar content. These candidate genes and beneficial alleles would be useful for improving soluble sugar content of soybean.